Kampung Semangga Jaya Sebagai Sentra Produksi Pakan Ternak Sapi - Abdul Rizal; Fredy Fredy; Adrianus Adrianus; Ineke Nursih Widyantari (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2021)
Semangga Jaya Village, Merauke Regency as one of the villages that has high rice productivity. In 2019 rice production was 55,184.34 tons with a harvested area of 9,614 hectares. This figure is a potential benefit for the community. However, the high production of rice is not followed by the interest of farmers in utilizing rice straw waste to be processed into products that have high economic value, namely into complete feed that can be used as cattle feed. Cattle farming business is currently starting to be developed by farmers, although in practice it has not been fully maximized. This is due to the lack of public understanding of cattle development and the feeding system used is still simple or uses rice straw which basically has a high crude fiber content. The implementation of this activity will provide full participation in solving problems faced by cattle farmer groups, especially the feed processing system by utilizing rice straw waste into complete feed. Semangga Jaya Village, Merauke Regency in the future can be used as a center for cattle feed production. The implementation of activities includes counseling and technical guidance as a medium for transferring knowledge and technology to partners, which will be carried out en masse, through groups and individuals while still implementing Covid-19 health protocols. The solutions offered in the implementation of the program are through non-physical and physical activities. It is hoped that (a) Increased knowledge and skills of farmers regarding the system for processing rice straw waste into complete feed, (b) Increased knowledge and skills in feeding cattle by looking at feed quality standards, (c) Increased knowledge and ability of farmers and breeders to produce feed into attractive packaging for sale through offline and online systems.